Metode User Centered Design untuk Mengembangkan Aplikasi Distribusi Produk Berbasis Mobile - Defriani, Meriska; Resmi, Mochzen Gito; Permana, Okta Amien (Sinkron : jurnal dan penelitian teknik informatika, 2021)
Anyelir Cake And Bakery is the largest cake shop in Purwakarta which is engaged in the production of various kinds of cakes. In the process of distributing products from the central store to branch stores, they still use WhatsApp to place orders. This causes frequent discrepancies in the number of products requested and the number of products received due to an error in reading the message. In this study, a mobile-based application will be built that is able to manage order data more accurately. The development of this application uses the User Centered Design (UCD). This is a design method that focuses on user needs so that the final result of this application does not need to change user behavior when using the application. The UCD method consists of four stages, namely plan the human centered design, specify user and organizational requirements, product design solutions, and evaluate design against user requirements. In the development process, application testing was carried out to get feedback from users with good scores, namely an average of 4 (agree) and 5 (strongly agree). This shows that the application is in accordance with the needs of the user.